2017
DOI: 10.17352/2455-5479.000027
|View full text |Cite
|
Sign up to set email alerts
|

Healthful School Environment: A Comparative Study of Public and Private Primary Schools in Ogun State, Nigeria

Abstract: Introduction: A healthy school environment (physical, biological and socio-cultural) serves as a major determinant of health and greatly infl uences the individual's level of intellectual growth and development. This study was therefore designed to assess the school environmental health services in both private and public primary schools in Ogun state Nigeria. Methods:The study was a comparative cross-sectional survey of Private and Public Primary Schools in Ogun state, Nigeria conducted between February and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
2
3
0
Order By: Relevance
“…This finding aligns with those of other studies in India and sub-Saharan Africa 15,27. Students also reported concerns about lack of soap and water similar to the findings ofAmoran et al (2017) in Ogun State, Nigeria.…”
supporting
confidence: 90%
See 2 more Smart Citations
“…This finding aligns with those of other studies in India and sub-Saharan Africa 15,27. Students also reported concerns about lack of soap and water similar to the findings ofAmoran et al (2017) in Ogun State, Nigeria.…”
supporting
confidence: 90%
“…This is predicated upon the alarming rate of toilet inaccessibility, inadequate or lack of functional toilets, poor sanitary conditions of available toilets, and high student to toilet ratio in public schools compared with their private counterparts. 5,28 Bisi-Onyemaechi and colleagues (2016) also reported grossly inadequate toilet facilities in certain public schools in Enugu and a standard rate of student to toilet ratio of 30:1 in a few PSs, which was also linked to affect the students' wellbeing. 29 The grossly inadequate state of sanitation facilities most probably leads to long queues at the toilet causing students to miss classes, whereas others will have to go far into the bush, field, or secluded spaces to get a semblance of privacy, which predisposes them to diverse health risks such as tears from sharps like thorns and broken bottles, attack from biting insects and animals like snakes and scorpions, and incidences rape.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the schools practice open dumping. This practice is not peculiar to the current study, as other studies reported similar findings [4,7,[18][19][20]. Open dumping of refuse serves as a breeding site for flies, mosquitoes, and rodents.…”
Section: Discussionsupporting
confidence: 79%
“…Policy (NSHP, 2006) Various research conducted in developing countries, for instance, in Nigeria (Amoran et al, 2017;Odeyemi & Chukwe, 2015), Myanmar (Htun et al, 2013), Iran (Abolli, etal., (2018) (Ajzen, 1985;1991;Dearing & Cox, 2018;Fishbein & Ajzen, 2010;Jones, et al, 2015). These theories served as a guide for were not at all interested while 4% were not sure.…”
Section: Introductionmentioning
confidence: 99%